Analyzing The Quality Control Of Milk Production Using Statistical Process Control (Spc) Method In CV. Cita Nasional - Teja Wicaksana; Lasmono Tri Sunaryanto (UNIVED Press, Universitas Dehasen Bengkulu, 2021)
Farming becomes one of the parts of agriculture development which has values in supplying the food needs in Indonesia. Now, the milk quality from dairy farmers is still below the standard determined by the dairy company, so it causes the milk’s selling price is staying low. Statistical Process Control (SPC) is a device to ensure the production process has qualified the standards and it also functions in supervising the production quality. This research aims to analyze the breakdown and its factors that influence it in CV. Cita Nasional’s milk production. This research used quantitative descriptive approach, a research that describes the occurring events to explain and solve the studied problem. This study used some ways of data collection method, which are: observation, interviews, and documentation. Furthermore, the data analyzing was using assistant device of Statistical Process Control (SPC). Check sheet, Pareto diagram, Histogram, Control chart, Cause and effect diagram. From the calculation result using Statistical Process Control (SPC) (Control Chart) tool aid, we can know about the greatest damage in milk production in CV. Cita Nasional, which is the damage due to 2026, 1 liters of leaking milk, the damage due to the different milk volume with the number of 871, 6 liters damage, and the damage caused by broken packaging with the numbers of 992, 2 liters.